Comparison of Moving Average, Single Exponential Smoothing, and Trend Analysis Forecasting Methods on Art Board Production Demand (Case Study of PT Pindo Deli Pulp and Paper Mills 1) - Monica Widya Putri; Fahriza Nurul Azizah (School of Industrial and System Engineering, Telkom University, 2021)
One of the companies engaged in the manufacturing industry is PT Pindo Deli Pulp and Mills 1, whichproduces various kinds of paper and tissue. Art Board is a type of paper produced by PT Pindo Deli Pulpand Mills 1, and is quite attractive to customers. However, customer demand for Art Board products oftenfluctuates. Product demand is an important aspect to be evaluated, because if the company does not planproperly the company will experience financial losses. Forecasting can be used as a support for companydecision making. Moving Average, Single Exponential Smoothing, and Trend Analysis are the methodsused to support forecasting in this study, where the next step is to analyze the accuracy of the forecastingmethod with the parameter values of MAD, MSE, standard error, bias, and forecasting for the next period.Based on data collection and analysis, it is found that the period 1 moving average method is the bestmethod for forecasting production demand for Art Board products with forecasting for the next period of19410 units, MAD of 3186,182, MSE of 16001250, and a bias of 634,546 meanwhile the standard error is4422,339.